Indo-French Strategic Symbiosis: Implications for Strategic Stability in South Asia - Sufian Ullah (CISS Insight Journal, 2024)
How does the Indo-French strategic alliance manifest, and what are its implications for the regional strategic stability of South Asia? This paper examines the above critical question by analyzing the alignment of France and India in advancing their respective strategic interests within the contemporary geopolitical landscape. Beyond economic and commercial synergies, the partnership is strategically oriented toward countering China’s growing influence in Asia-Pacific. This paper identifies and evaluates the primary factors driving the Indo-French strategic alignment, tracing its historical evolution and examining its manifestations in enhanced cooperation in nuclear technology, advanced defense capabilities, and military modernization. These developments are analyzed in the context of South Asia’s strategic stability, emphasizing how the deepening partnership supports India’s assertive strategic posture and military ambitions, thereby exacerbating the region’s security dilemmas. Furthermore, the paper critically assesses the implications of joint efforts in developing nuclear-capable platforms, such as the Rafale fighter aircraft, and how these efforts challenge the principles of the nuclear non-proliferation regime. Through this analysis, the article highlights the broader ramifications of the Indo-French partnership for the regional security dynamics of South Asia.